A Comprehensive Community of Inquiry Framework for Exploring Technology Enhanced Language Learning - Irum Alvi (IAFOR Journal of Education, 2022)
The use of technology for second language (L2) acquisition has become ubiquitous, but little thought has been given to the factors that impact the language learning experience. This study aims to use the Community of Inquiry (CoI) framework to propose and validate a more comprehensive model for investigating the influence of presence on learners’ L2 learning experience using Technology Enhanced Language Learning (TELL). Data were collected from a sample of language learners (n = 129) studying in the State of Rajasthan, India using an e-questionnaire. To scrutinize the effect of various forms of presence, descriptive and inferential analyses were conducted. The findings suggest strong, positive, and statistically significant associations exist between the original CoI elements (teaching presence, cognitive presence and social presence), the newly added elements (learning presence, emotional presence, and technological presence), and learning experience. These results confirm the idea that presence can hinder and/or enhance L2 learning experiences. No association was found between technical barriers and learning experience. The findings have theoretical and practical implications. The results suggest the value of expanding the CoI framework, scrutinizing the learners’ experience, analyzing the influence of presence, and enriching the application of the technology for language learning. Such results may ensure TELL courses are designed as vigorous learning environs which facilitate language acquisition.